Big data initiatives by governments – issues and challenges : A review - Zainal, Noor Zalina; Hussin, Husnayati; Mior Nazri, Mior Nasir (IEEE, 2017)
In this modern era, we are living in the age of big data. All over the world recently, the organizations including the government is taking initiative to adapt and implement big data. Nowadays, government do not want to only collect data, but they want to understand the meaning and the significance of the data, as well as to analyze the data and aid them in making strategic decisions. This paper is aimed to review on the definition of big data and e-government specifically, also reviews the initiatives of big data on government in several countries, including highlights on issues and challenges peculiar to the big data initiatives.